ANALISIS TAYANGAN FILM NUSSA DAN RARA TERHADAP PENANAMAN NILAI MORAL DAN AGAMA ANAK USIA DINI - Azka Pia Nur Latifah; Fitri Febri Handayani; Naili Rohmah (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
This study aims to analyze the moral and religious values contained in the animated film Nussa and Rara. The method used in this study is descriptive qualitative with data collection techniques. The data collection process was carried out by watching the film in its entirety and recording information related to moral values in the storyline. Based on the results of the analysis, a number of moral and religious values were found displayed in the film, namely: mutual assistance, mutual respect, personal and environmental hygiene, compassion, politeness, willingness to sacrifice and kindness, empathy and facing injustice, the value of introducing the pillars of Islam and carrying out worship, the value of sincerity and honesty, tolerance, table manners, learning to be sincere and accepting destiny with gratitude, the importance of reading basmalah and learning from mistakes, the value of gratitude and charity, the value of mahram and being wise in acting. The results of this study indicate that Nussa and Rara is an educational show that is suitable for use as a medium for learning moral values in early childhood. Therefore, this film can be used by educators as a means of learning fun and educational characters. This can be an insight into knowledge about cartoon films that have positive moral messages besides Nusa and Rara. So parents need to identify children's films positively for the growth of early childhood.